PEMBERDAYAAN ARBITRASE SEBAGAI LEMBAGA PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DI LUAR PENGADILAN DALAM PERSPEKTIF POLITIK HUKUM - Gindo L. Tobing (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Arbitration is not well known, especially by the workers/laborers because of lack of internalization by the government, trade unions/workers and by employers. So until now there has been no industrial disputes are resolved through arbitration. With a variety of reasons the parties prefer the Industrial Relations Court (PHI) rather than arbitration and other settlement alternatives (conciliation) even prescribed pattern that justice can only be obtained through the courts alone. Changing the paradigm so that people do not always think only through PHI, justice and legal certainty can be obtained (justice in many rooms) arbitration should be empowered to propose improved regulation (amendment through MK), the institutional approach, culture, law. Model arbitration offered so-called Arbitration Pancasila because at each stage of the examination should be preceded by consensus, peace. Legal political perspective of stakeholders will give birth to the dispute settlement mainstreaming regulation on fairness, expediency and legal certainty through arbitration institutions.Kata Kunci: Pengadilan Hubungan Industrial, Pemberdayaan Arbitrase, Model Arbitrase dan Perspektif Politik Hukum